Cognitive Therapies Do Not Ignore Affect - Martin, Jack (Canadian Journal of Counselling and Psychotherapy, 2011)
Arguments are offered to support the claims that cognitive therapies are now, and always have been, concerned with human affective experience, and that these therapies are not limited to conscious, rational, affectively-neutral concerns or difficulties. Examples are cited of healthy programs of research and theoretical development in cognitive psychology that provide support and direction to contemporary cognitive therapies. Clarification of misconceptions about the cognitive therapies is important because of the promise these therapies hold for integrating theoretical and empirical work in academic-experimental and applied areas of psychology.